Digital Banks in Algeria: A study of the Bank of Algeria regulation 24/04 - BOUFAMA, Samira (Journal of Human Sciences, 2025)
In the context of rapid advancements in the digital age, digital banks have emerged as transformative innovations, fundamentally reshaping the way individuals and businesses access financial services. By harnessing modern technology, these banks provide a comprehensive array of financial services without requiring customers to visit physical branches, thereby offering unparalleled convenience and flexibility. In Algeria, the legislator has undertaken significant steps to regulate digital banking activities as part of efforts to modernize the national banking system. This is reflected in the enactment of the new Monetary and Banking Law 23-09 and the subsequent issuance of Bank of Algeria Regulation 24-04, which outlines the specific conditions for licensing, establishing, and operating digital banking activities.